Konstruktion och tillverkning av en klocka med fokus på klassisk mekanik - Cronheden, Robin; Engström, Arvid; Gelang, Hampus; Ghazy, Zahran; Gustafsson, Amanda; Salim, Sheyma (My University, 2024)
This report focuses on the construction and analysis of a mechanical clock by applying theoretical and practical methods from mechanics and machine elements. The goal was to develop both a physical and an analytical model that could be examined and analyzed. The analytical model was based on detailed motion equations and kinematics, while the physical model was constructed using manufacturing techniques such as 3D printing and traditional wood and metalworking. By comparing the results from the physical model with theoretical calculations, the accuracy of the analytical model could be calibrated and improved. The experiments showed that through careful control and adjustment of the components, the clock could maintain an operating time of almost 45 hours with a minimal margin of error, surpassing the project’s goals. The project particularly highlights the challenges of friction, which proved to have a significant impact on the clock’s performance. Managing and minimizing friction was crucial for achieving high precision, and insights from these experiences contributed to a better understanding of how mechanical systems can be optimized. The conclusion of the work is that the integrated application of mechanical and mathematical principles is essential for developing precision systems. The project also emphasizes the importance of iterative design and testing to achieve optimal performance in mechanical constructions.
Keywords: Mechanical clock; 3D-printing; horology; watchmaking; analytical modelling